Bł. Jan Henryk Newman - etos i nawrócenie - Kłos, Jan (Studia Europaea Gnesnensia, 2016)
This paper is an attempt to approach the history of bl. John Henry Newman as the history of a man who decided to re-evaluate his ethos in line with what his conscience showed him to be a duty to fulfil. Here conversion is understood as a long process of development, where the moment of decision is only the finał element. What seems to be an illumination and impulse is only seemingly a sudden change. In faet, it stems from personal and tacit thought, from the mystery of the person.